Kinerja Microbial Fuel Cell dengan Variasi Hambatan Eksternal dalam Menghasilkan Energi Listrik dan Menyisihkan Senyawa Organik pada Limbah Cair - Hidayat, Syarif; Aghnia, Dini Widyani; Kardena, Edwan; Helmy, Qomarudin (Universitas Diponegoro, 2020)
wastewater into direct electrical energy. In this study, the applied external resistance in the MFC reactor was optimized to determine its optimum conditions in generating electrical energy and removing organic compounds in wastewater. The MFC reactor's performance was evaluated by cell potential, power density, Coulombic efficiency (CE), and organic removal efficiency. The purpose of measuring these parameters is to determine the MFC reactor's performance in producing electrical energy and removing organic compounds for each experiment variation. Biochemical tests were carried out to choose the type of microorganisms in the anode electrode. This measurement is essential for the optimization of environmental conditions for subsequent experiments. MFC reactor with 100 Î© was selected as an optimum condition since it produced the highest power density and efficiency organic removal. In this condition, the CE value was 57%, slightly lower than the MFC reactor with an external resistance of 50 Î©, 65%. Based on biochemical tests, microorganisms that grow on the anode electrode were closed to the Clostridium (Clostridium sp1 and Clostridium sp2), a type of bacteria that belongs to the class of the exoelectrogen. The results showed that the applied external resistance influenced the performance of the MFC reactor. Thus the selection of the proper external resistance is an essential factor in the MFC reactor's operation.